Functionalization of carbon nanomaterials - Mitura, K. A.; Szczypiński, M. M.; Korn, Ł.; Czerwińska, E.; Kolesińska, B. (Wydawnictwo Politechniki Łodzkiej, 2018)
"Nowadays, almost all food products that require transport or storage, which we buy in stores are stored in packages. The packaging still needs to be modified to meet the needs of the market and to optimize the shelf life of the product as much as possible. These requirements have meant that the packaging industry has become a dynamically developing field, and entrepreneurs making pink implement new technological solutions. In order to extend the shelf life of food, smart and active packaging is introduced to eliminate the processes that terminate products inside. Currently, many studies focus on bioactive packaging modified with various allotropic forms of carbon. Bearing in mind the excellent biological properties of the nanodiamond, it finds its application in food packaging. This paper presents the adhesive and antioxidant properties of functionalized and non-functionalized nanodiamond particles and graphene oxide (GO)."

"W dzisiejszych czasach prawie wszystkie produkty spożywcze, które wymagają transportu lub przechowywania, są przechowywane w paczkach. Opakowania wciąż muszą być ulepszane, aby sprostać potrzebom rynku i aby mogły maksymalnie zoptymalizować okres przydatności produktu do spożycia. Wymagania te sprawiły, że branża opakowaniowa stała się dynamicznie rozwijającą się dziedziną, a przedsiębiorcy wprowadzają nowe rozwiązania technologiczne. Aby wydłużyć okres przydatności do spożycia żywności, wprowadzono inteligentne i aktywne opakowania, które eliminują procesy starzenia przechowywanego produktu. Obecnie wiele badań koncentruje się na bioaktywnych opakowaniach modyfikowanych różnymi alotropowymi formami węgla. Mając na uwadze doskonałe właściwości biologiczne nanodiamentu, znajduje on również zastosowanie w pakowaniu żywności. W artykule przedstawiono właściwości adhezyjne i przeciwutleniające funkcjonalizowanych i niefunkcjonalizowanych cząstek nanodiamentu i tlenku grafenu (GO)."
Keywords: bioaktywne opakowania; nanodiament; tlenek grafenu; bioactive packaging; graphene oxide; nanodiamond